2019
DOI: 10.1002/ecm.1394
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal patterns of microbial composition and diversity in precipitation

Abstract: Microbes in the atmosphere have broad ecological impacts, including the potential to trigger precipitation through species and strains that act as ice nucleation particles. To characterize spatiotemporal trends of microbial assemblages in precipitation we sequenced 16S (bacterial) and 18S (fungal) rRNA gene amplicon libraries collected from 72 precipitation events in three U.S. states (Idaho, Louisiana, and Virginia) over four seasons. We considered these data from the perspective of a novel metacommunity fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 121 publications
1
11
0
Order By: Relevance
“…When compared to low intensity rainfall, moderately intense rainfall produces larger drop sizes, which tend to be more efficient at scavenging below-cloud aerosols (Figure 4). Our results are consistent with recent observations showing the fungal composition of rain correlated with lower altitude characteristics of storms, whereas the smaller-sized bacteria assemblages correlated with macroscale drivers that implied nonlocal sources [45]. It should be noted our calculations have ignored the contribution of microbial aerosols within the cloud that are subject to scavenging as drops descend through the cloud.…”
Section: Discussionsupporting
confidence: 90%
“…When compared to low intensity rainfall, moderately intense rainfall produces larger drop sizes, which tend to be more efficient at scavenging below-cloud aerosols (Figure 4). Our results are consistent with recent observations showing the fungal composition of rain correlated with lower altitude characteristics of storms, whereas the smaller-sized bacteria assemblages correlated with macroscale drivers that implied nonlocal sources [45]. It should be noted our calculations have ignored the contribution of microbial aerosols within the cloud that are subject to scavenging as drops descend through the cloud.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, another study showed that diurnal cycles in the boundary layer resulted in fungal and bacterial aerosols shifting with temperature, humidity, and CO 2 conditions 48 . Both dry and wet deposition significantly influence bioaerosol patterns and it is worth emphasizing our flights occurred in non-cloudy, precipitation-free areas 49 . With a multiyear campaign lasting seven years at an alpine field site in Spain, dynamic, seasonal shifts in 16S rRNA measurements (yielding mostly Alphaproteobacteria and Betaproteobacteria) were found 4 .…”
Section: Discussionmentioning
confidence: 99%
“…(iv) Potential phylogenetic and geographic sources of ice-nucleating bacteria. The 16S rRNA gene sequences from 45 of the 65 precipitation events were successfully amplified, sequenced, and analyzed (69). Of the OTUs that correlate significantly with INP concentrations (Table S6), many are related to bacterial taxa documented in soils, plant ecosystems, air, and precipitation (69,114,115).…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA gene sequences from 45 of the 65 precipitation events were successfully amplified, sequenced, and analyzed (69). Of the OTUs that correlate significantly with INP concentrations (Table S6), many are related to bacterial taxa documented in soils, plant ecosystems, air, and precipitation (69,114,115). Although there were no significant trends between INPs and the known ice-nucleating genera Pseudomonas or Pantoea, there are significant correlations between OTUs from Xanthomonadaceae (i.e., containing the IN species Xanthomonas campestris) and the total Ϫ5 to Ϫ11 , total Ϫ11 to Ϫ14 , and bio Ϫ5 to Ϫ10 factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation